Evaluation of rituximab therapy in real clinical practice (according to the OREL registry of patients with rheumatoid arthritis - A. S. Avdeeva; A. M. Satybaldyev; N. V. Demidova; N. Yu. Nikishina; E. V. Gerasimova; N. V. Muravyeva; G. I. Gridneva; O. A. Rumyantseva; K. A. Kasumova; A. V. Alekseeva; N. V. Chichasova; D. A. Kusevich; et al. (Научно-практическая ревматология, 2019)
Objective: to analyze therapy with rituximab (RTM) in real clinical practice according to the data available in OREL registry of patients with active rheumatoid arthritis (RA).Subjects and methods. The analysis included 349 patients. All the patients received RTM: 340 – the original drug (MabThera®) and 9 – the biosimilar Acellbia®. 263 patients (75.4%) received RTM in combination with disease-modifying anti-rheumatic drugs (DMARDs) and 86 (24.6%) – RTM as monotherapy.Results and discussion. Of the 349 patients included in the analysis, 272 (77.9%) patients received RTM as the first biologic agent (BA) (263 patients were treated with the original drug and 9 – with the biosimilar) and 77 (22.1%) patients had previously used the BA. The majority of patients (n=205 (58.7%)) received three or more; 109 (31.2%) patients – one, and 35 (10%) – two RTM courses of RTM therapy. RTM caused a significant reduction in disease activity just after the first therapy course and in the levels of acute-phase reactants (C-reactive protein (CRP) and ESR); after the fifth therapy course, median CRP concentration decreased by 1.4 times and amounted to 7 [1.2; 17.9] mg/l and that of ESR reduced by 1.8 times and was 10 [5; 20] mm/hr (p<0.05).Conclusion. The analysis of RTM therapy in RA patients in real clinical practice demonstrated that in most cases RTM was given as the first BA, in combination with DMARDs, the main agent of which was methotrexate. The use of RTM was accompanied by a significant reduction in disease activity and in the serum levels of acute-phase reactants and autoantibodies.